The application of hepatopancreatoduodenectomy in advanced gallbladder carcinoma: Patient selection, surgical outcomes and influence on survival compared to radical cholecystectomy - Manar Mikhail Atyah; Yingjixing Luo; Ruyi Liu; Zhiying Yang; Li Xu (Asian Journal of Surgery)
Aim: to investigate hepatopancreatoduodenectomy (HPD) application in gallbladder carcinoma (GBC) and compare it to radical cholecystectomy (RC) regarding patients’ characteristics, surgical outcome and survival. Methods: Patients treated in our center were included. Three groups (HPD, RC, no-surgery) were compared. Comparisons included basic characteristics, liver function, tumor biomarkers, surgical complications, outcome, and survival. Differences in severity, surgical risks and survival were investigated. Results: In total, 19 patients in HPD, 89 in RC and 20 in no-surgery groups were included. Median follow-up was 42.0 months. Compared to RC, HPD group revealed increased severity represented by significantly higher rates of elevated ALT, AST, TB, DB, preoperative biliary decompression, T3/4, N1/2, stage III/IV, and MVI. Similar severity was observed between HPD and no-surgery groups. Additionally, HPD presented higher risks of perioperative bleeding, transfusion and complications (grade III/IV). Pancreatic fistula and delayed gastric emptying were most encountered in HPD and only one mortality was recorded. Although HPD had shorter survival in general population (HPD: 17 ± 5.804, RC: 49 ± 11.433,P < 0.001); however, in matched (PSM) advanced stages, its benefits matched RC (HPD: 17 ± 4.793, RC: 11 ± 1.169, P = 0.966). Significant survival advantages were observed when comparing HPD to no-surgery group (HPD: 17 ± 5.804, no-surgery: 7 ± 0.836, P = 0.013). Conclusion: Cases benefiting from HPD are usually severe and comparable to unresectable cases. Although HPD complexity and complication risks are higher than RC, the survival benefits of HPD in advanced GBC stages are not inferior. Thus, HPD is a valuable option in such patients and can be the only approach to achieve R0 resection.